Distributive leadership as predictor of 21st century teaching practices - Nantah Ponnusamy; Arumugam Raman (Institute of Advanced Engineering and Science, 2024)
The concept of distributive leadership is a vital component of 21st century teaching practices. This study aimed to identify the dimensions that influence the development and implementation of science and mathematics teaching in dual language program schools. It was conducted with the help of over 336 teachers from 93 dual language program (DLP) schools in Malaysia. The distributive leadership readiness scale and 21st century skill (4C) questionnaire was used to collect data and analyze the effects of various dimensions on the development and implementation of science and mathematics teaching in dual language program schools. The results of the study revealed that the P3 model was associated with 14.9% (=.149) increase in the variance of 21st century teaching practices. The results of the analysis revealed that the changes in the three leadership style components included in the regenerating model were significant. The shared responsibility, leadership style and the combination of these dimensions contributed to the 12.9% (=.129) increase in variance. The research also found a positive relationship between 21st century teaching practices and the distributive leadership concept. The findings support the notion that distributive leadership can be a weak factor influencing the development and implementation of 21st century teaching practices.